2004
DOI: 10.1007/s11199-004-0716-z
|View full text |Cite
|
Sign up to set email alerts
|

Reason to Believe: Representations of Aggression as Phenomenological Read-Out

Abstract: Men tend to view their own aggression as an instrumental act aimed at imposing control, whereas women tend to view theirs as an expressive act resulting from a loss of self-control. These interpretations have been called social representations based on their presumed social origins and mode of transmission. However, if women's self-control is generally higher than men's, they would be expected to behave aggressively only infrequently and at higher levels of provocation. Aggression would be experienced phenomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 70 publications
1
14
0
5
Order By: Relevance
“…This was puzzling because it seemed reasonable to suppose that holding a self-condem- natory view of aggression should be strongly and inversely associated with aggressive behaviour. However, recent studies have shown that, in both sexes, expressive individuals not only view aggression as an index of poor self-control but actually possess better self-control than their more instrumental peers [Alexander et al, 2004;Driscoll et al, 2006]. This raises the question of whether the anger of expressive-minded individuals is simply ''squashed'' or whether it is expressed in other forms that are not detected by standard aggression inventories.…”
Section: Discussionmentioning
confidence: 99%
“…This was puzzling because it seemed reasonable to suppose that holding a self-condem- natory view of aggression should be strongly and inversely associated with aggressive behaviour. However, recent studies have shown that, in both sexes, expressive individuals not only view aggression as an index of poor self-control but actually possess better self-control than their more instrumental peers [Alexander et al, 2004;Driscoll et al, 2006]. This raises the question of whether the anger of expressive-minded individuals is simply ''squashed'' or whether it is expressed in other forms that are not detected by standard aggression inventories.…”
Section: Discussionmentioning
confidence: 99%
“…They are, therefore, less able to control or restrain their emotions or behavior, and are more likely to express their anger in the form of overt aggression than are those with high self-control. They will, therefore, tend to act impulsively in response to provocation (Alexander, Allen, Brooks, Cole, & Campbell, 2004;Driscoll et al, 2006).…”
Section: Variables Used In the Current Studymentioning
confidence: 99%
“…At least in Western cultures, men tend to accept and use bodily force more easily than women (Felson, 2002). Consequently, men are more likely to associate their own use of physical force with gaining influence, whereas women are less likely to do so (Alexander, Allen, Brooks, Cole, & Campbell, 2004;Driscoll, Zinkivskay A., Evans, & Campbell, 2006;Eagly & Steffen, 1986;Campbell, 1999). This makes men more likely to experience making a fist in situations in which they want to achieve or actually achieve power.…”
Section: Making a Fist And The Embodiment Of The Self's Powermentioning
confidence: 99%